Pengaruh Kompetensi Terhadap Kepuasan Dan Motivasi Yang Berdampak Pada Kinerja Karyawan Koperasi Aneka Jaya Batur Ceper Klaten - Apriyono, Aan (STIE AUB Surakarta)
The purpose of this study to determine empirically and analyze the effect on satisfaction and motivation competencies that impact on employee performance Aneka Jaya Cooperative Batur Ceper Klaten. The analysis technique used is to use a test instrument that includes the validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. Competence positive and significant impact on satisfaction. Competence positive and significant impact on the motivation. Competence positive and significant effect on the performance of employees. Satisfaction and no significant positive effect on the performance of employees. Motivation positive and significant effect on the performance of employees. The F test results can be concluded jointly competence variables, satisfaction and motivation affects employee performance in the Cooperative Aneka Jaya Batur Ceper Klaten. R2 value of 0.71 means total variation in the Cooperative Employee Performance Aneka Jaya Batur Ceper Klaten explained by the variable competence, satisfaction and motivation of 71% and the remaining 29% described other variables outside the model as an example of research training and career paths. The results of path analysis, it can be concluded that the effect of variable competence of the performance is the most effective path.Keywords: Competence, Job Satisfaction, Motivation, Employee Performance